The Timing of Asset Sales and Earnings Manipulation - Bartov, Eli (The Accounting Review, 1993)
[This study presents an empirical examination of whether managers manipulate earnings through the timing of income recognition from disposal of long-lived assets and investments (hereafter assets). Since managers can often choose the period during which an asset will be sold, and since the principle of acquisition cost underlying the accounting valuation of assets implies that changes in the market value of an asset between acquisition and sale are reported in the period of sale, it follows that there are opportunities for managers to manipulate earnings through the timing of asset sales at relatively low cost. Two common explanations for earnings manipulations are examined: the earnings-smoothing and the debt-equity hypotheses.1 The earnings-smoothing hypothesis predicts that earnings are manipulated to reduce fluctuations around some level that is considered normal for the firm (see, e.g., Ronen and Sadan 1981, 6). The debt-equity hypothesis suggests a positive relation between a firm's debt-equity ratio and managers' choice of earnings-enhancing activities (see, e.g., Watts and Zimmerman 1986, 200-21).2 The findings are consistent with the timing of asset sales by managers so that the recognized income from these sales smooths intemporal earnings changes and mitigates accounting-based restrictions in bond covenants. The results also show that the earnings-smoothing and the debt-equity effects are incremental; after controlling for one effect the other still exists. Finally, sensitivity analysis showing that these results are robust to specifications that consider asset sale levels, bonus plans, possible tax effects, and financial soundness suggests that the findings are not attributable to misspecified statistical tests. The results of this study may be relevant to the ongoing debate about dropping the principle of acquistion cost underlying the accounting valuation of assets in favor of the principle of current cost (see, e.g., The Wall Street Journal 1990b). While the former is considered reliable, the latter is said to be vulnerable to earnings manipulations because net income is materially affected by management opinion on the sale values of the assets involved (see, e.g., Kieso and Weygandt 1987, 35). The evidence in this study suggests that, despite its reliability, managers take advantage of the acquisition-cost principle to manipulate earnings. This should be considered when evaluating the advantages and disadvantages of acquisition-cost accounting relative to current-cost accounting.]